Prevenção de conflitos médico-legais no exercício da medicina - Minossi, José Guilherme [UNESP] (Colégio Brasileiro de Cirurgiões, 2009)
Os conflitos médico-legais que ocorrem no exercício da Cirurgia e da Medicina são motivos de preocupação não só no meio médico, mas também na sociedade como um todo, pois se de um lado geram um maior desgaste emocional ao médico, por outro, os pacientes estão sendo rejeitados. As causas desses conflitos são muitas, envolvendo fatores não assistenciais, como o sistema de saúde distorcido e desorganizado, a falta de participação da sociedade e do médico na melhoria desse sistema, o aparelho formador que lança no mercado grande número de jovens médicos despreparados para o exercício dessa nobre profissão, além da falta do ensino continuado. A solução para esses conflitos não poderá ser por meio de simples criação de leis, e nem pela negativa da existência do erro médico, que ocorre numa freqüência até maior do que os próprios conflitos. Todavia, pode-se afirmar que é muito importante melhorar a relação médico-paciente. É necessário, ainda, que o médico conheça a fundo seus deveres de conduta e que, principalmente, se abstenha de praticar abusos do poder. A sociedade deve também entender que a saúde não é uma questão exclusiva dos médicos e que deve lutar pela melhoria das condições dos níveis de vida.

Generally, medico-legal conflicts which occur in surgical and medical practice are a source of worry for both the medical profession and the society as a whole, because on one hand, they could cause high emotional stress for doctors, and on the other hand, patients could be rejected. Once consolidated, defensive medicine increases treatment costs and the doctor-patient relationship could transform into a tragedy. There are many causes for this, including non-treatment factors, such as an unsupported and disorganized health system, lack of participation from society and the doctor in improving this system, the training machine which launches a large number of young unprepared doctors to practice in this noble profession, along with a lack of continuing training, as there are few public or private institutions providing preparation, or further medical training. The related treatment factors are generally, a deficient doctor-patient relationship, poor work condition, power abuse by the doctor, a lack of clear agreement, and poor medical record keeping. These conflicts cannot be solved by simple creating legislation, or by denying the existence of medical error, which occurs at higher frequency than the actual conflicts. It is very important to improve the doctor-patient relationship because an effective fraternal relationship reduces the chance of a judicial demand. The doctor still needs to fully understand his/her conduct obligations and mainly to avoid power abuse. Doctors must also professionally link themselves with politicians who fight for the individual's rights against the system. Society must also understand that health is not just an issue exclusive for doctors, and people must fight to improve living conditions. Society must seriously show its frustration with the increasing disparity between scientific possibilities and actual wellbeing. The training machine needs immediate profound changes to produce professionals with the highest qualifications equipped for the needs of our population.
Prevention of medico-legal conflicts in medical practice
Keywords: Erros Médicos; Cirurgia; Ética médica; Responsabilidade legal; Medical errors; Surgery; Ethics; Medical; Liability legal